2017
DOI: 10.1063/1.4982884
|View full text |Cite
|
Sign up to set email alerts
|

Entropic rectification and current inversion in a pulsating channel

Abstract: We show the existence of a resonant behavior of the current of Brownian particles confined in a pulsating channel. The interplay between the periodic oscillations of the shape of the channel and a force applied along its axis leads to an increase of the particle current as a function of the noise level. A regime of current inversion is also observed for particular values of the oscillation frequency and the applied force. The model proposed to obtain these new behaviors of the current is based on the Fick-Jaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…This description has been widely used in the study of transport properties in confined media and applied to physico-chemical and biological systems at the nanoscale, such as microfluidic channels, porous media, ion channels, and membrane transporters. 14,15,21,37,41 In this article, we will use this approach to study the resonant behavior of Brownian particles moving in a deformable channel, analyzing the energy efficiency and the optimization of particle transport. We will compare the results obtained with Brownian dynamics (BD) simulations carried out on the basis of the Langevin equation.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This description has been widely used in the study of transport properties in confined media and applied to physico-chemical and biological systems at the nanoscale, such as microfluidic channels, porous media, ion channels, and membrane transporters. 14,15,21,37,41 In this article, we will use this approach to study the resonant behavior of Brownian particles moving in a deformable channel, analyzing the energy efficiency and the optimization of particle transport. We will compare the results obtained with Brownian dynamics (BD) simulations carried out on the basis of the Langevin equation.…”
Section: Modelmentioning
confidence: 99%
“…39,40 It has also been shown that channel deformations can cause resonances and anti-resonances that may have an impact on transport properties. 37,[41][42][43] The question, therefore, arises as to whether there are optimal conditions for transport in this case that take into account the fact that the canals cannot be considered isolated from the environment. This is precisely the aim of this article.…”
Section: Introductionmentioning
confidence: 99%
“…Such a scenario can be realized by means of optical, electric or magnetic fields [17][18][19] or by forces resulting from the geometrical confinement of the particles. This is the case of the ondulatory motion of worm-like organisms [20,21], peristaltic pumping [22][23][24][25], fluctuating ion channels and pores [26][27][28][29][30][31][32][33][34][35][36][37] as well as synthetic soft micro-nanofluidic devices [38][39][40]. Knowing what the impact of higher order harmonics is on the response of the system is a question of great current interest.…”
Section: Introductionmentioning
confidence: 99%
“…Such a scenario can be realized by means of optical, electric or magnetic fields [26,42,48] or by forces resulting from the geometrical confinement of the particles. This is the case of the ondulatory motion of worm-like organisms [20,33], peristaltic pumping [34,35,37,38], fluctuating ion channels and pores [12-18, 21, 22, 31, 32, 36] as well as synthetic soft micro-nanofluidic devices [28][29][30]. Knowing what the impact of higher order harmonics is on the response of the system is a question of great current interest.…”
mentioning
confidence: 99%